Lewis Acid Catalyzed Rearrangement of Furylcarbinols: The Aza- and Oxa-Piancatelli Cascade Reaction - Palmer, Leoni I.; Read de Alaniz, Javier (Synlett, 2014)
The acid-catalyzed rearrangement of furylcarbinols is utilized to access 4,5-substituted cyclopentenones. This cascade transformation began with implementing anilines, as an alternative nucleophile to water as used in the Piancatelli rearrangement, and has currently progressed through an intramolecular rearrangement to the use of alcohols as the nucleophile.
Keywords: lanthanides; cascade; rearrangement; cyclopentenones; 4π electrocyclization